2019
DOI: 10.3389/fmicb.2019.01639
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Halotolerant Plant Growth Promoting Rhizobacteria From Durum Wheat (Triticum turgidum subsp. durum) Cultivated in Saline Areas of the Dead Sea Region

Abstract: Plant growth promoting rhizobacteria (PGPR) are beneficial microorganisms that can be utilized to improve plant responses against biotic and abiotic stresses. In this study, 74 halotolerant bacterial isolates were isolated from rhizosphere and endorhizosphere of durum wheat ( Triticum turgidum subsp. durum ) plants cultivated in saline environments in the Ghor region near the east of the Dead Sea. 16S rDNA partial sequences and phylogenetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 61 publications
7
74
0
Order By: Relevance
“…One of the prime responses of salt stress is that it slows down the efficiency of water uptake by the plants and disturbs the osmotic balance leading to apoptosis. In this situation, the compatible osmolyte proline activated and tried to mitigate the effects of salt [2]. Our results showed that the plants inoculated with the P. pseudoalcaligenes recorded significantly higher proline level and reduced malondialdehyde under salt stressed conditions in comparison to un-inoculated salt affected plants.…”
Section: Plos Onementioning
confidence: 80%
See 4 more Smart Citations
“…One of the prime responses of salt stress is that it slows down the efficiency of water uptake by the plants and disturbs the osmotic balance leading to apoptosis. In this situation, the compatible osmolyte proline activated and tried to mitigate the effects of salt [2]. Our results showed that the plants inoculated with the P. pseudoalcaligenes recorded significantly higher proline level and reduced malondialdehyde under salt stressed conditions in comparison to un-inoculated salt affected plants.…”
Section: Plos Onementioning
confidence: 80%
“…Plant-growth-promoting bacteria (PGPB) are capable of enhancing plant growth by colonizing plant roots that can benefit the plant [1]. Among those, the halotolerant PGPB can withstand higher concentration of salt [2]. Halotolerant PGPB can promote plant growth and indirectly develop tolerance against stress by altering the selectivity of Na + , K + , and Ca 2+ to sustain a higher K + /Na + ratio, regulating the various antioxidant enzymes levels in the cells.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations